Pulmonary Hypertension in Patient with Acyanotic Congenital Heart Defects in Abdul Wahab Sjahranie General Hospital, Samarinda from 2015-2016 - Vivi Widianto Tjan (Cardiovascular and Cardiometabolic Journal, 2020)
Background. Congenital Heart Defects (CHD) is the most common congenital disease that affects 8 out of every 1000 births. CHD can be classified as cyanotic and acyanotic. Acyanotic is the most frequently diagnosed CHD. The most common complication in acyanotic CHD is pulmonary hypertension. Aims. This descriptive study was based on medical records of acyanotic CHD patients with pulmonary hypertension in RSUD Abdul Wahab Sjahranie Samarinda during 2015 to 2016 who were diagnosed by cardiologist and confirmed with echocardiography. Methods. There were 62 patients diagnosed with acyanotic CHD and pulmonary hypertension which 58% of patients were diagnosed with Atrial Septal Defect (ASD), Ventricular Septal Defect (VSD) (21%), and Patent Ductus Arteriosus (PDA) (21%). Defect sizes distribution were mostly large (66%), then medium (29%), and small (5%). There were 56% patients diagnosed before 18 years old and 44% diagnosed after they reached 18 years old. There were 68% female patients and 32% male patients. Results. Pulmonary hypertension severity distribution were mild (52%), moderate (26%), and severe (22%). The most diagnosed acyanotic CHD was ASD. Defect size in acyanotic CHD was mostly large, and mostly found in female patients. The severity of pulmonary hypertension was mostly mild.